REALITY OF MEDIA TECHNOLOGIES IN THE CONCEPTUAL HORIZON OF RUSSIAN PHILOSOPHY - K. A. Ocheretyany (Дискурс)
The article advocates the possibility of applying approaches developed in the tradition of Russian philosophy to media reality analytics. The approaches of Russian philosophy with their understanding of being as meaningful reality and smart reality are extremely relevant in the situation of high-tech reality (smart media). The questions of consciousness networkization, techno-delegate sensory experience, and translation of everyday life into a media format are adequate to searches of the Russian thought: questions of the completeness of human self-realization, collegiality catholicity of the human community, sophianic nature of the creation.